New Insights Into the Role of Aberrant Hippocampal Neurogenesis in Epilepsy - Chen, Peng; Chen, Fuchao; Wu, Yue; Zhou, Benhong (Frontiers in Neurology, 2021)
Data accumulated over the past four decades have confirmed that adult hippocampal neurogenesis (HN) plays a key role in the wide spectrum of hippocampal pathology. Epilepsy is a disorder of the central nervous system characterized by spontaneous recurrent seizures. Although neurogenesis in persistent germinative zones is altered in the adult rodent models of epilepsy, the effects of seizure-induced neurogenesis in the epileptic brain, in terms of either a pathological or reparative role, are only beginning to be explored. In this review, we described the most recent advances in neurogenesis in epilepsy and outlooked future directions for neural stem cells (NSCs) and epilepsy-in-a-dish models. We proposed that it may help in refining the underlying molecular mechanisms of epilepsy and improving the therapies and precision medicine for patients with epilepsy.